'Happy Monday friends! Coffee?' Matteo Salvini, good morning selfies, and the influencer politician. Issue 3 (3rd July 2022) - Starita, Giovanni Daniele; Trillò, Tommaso
ABSTRACT: Social media have reshaped how people achieve, retain, and perform celebrity. This, in turn, has re-shaped how celebrity and politics intersect. We contend that the established concept of the 'celebrity politician' no longer captures all of the most common celebrity practices of highly visible political figures. This is because politicians increasingly model their public personae on internet celebrities. We substantiate this argument with an analysis of a specific micro-celebrity practice adopted by Italian populist leader, Matteo Salvini: the 'good morning selfie.' We argue that Salvini borrows the practice of good morning selfies from social media influencers to build perceived interconnectedness and affective intimacy with his audience of (prospective) constituents. We conclude that the ideal type of the celebrity politician can and should be updated for the digital age with a new figure we tentatively call the 'influencer politician'.